2022
DOI: 10.1038/s42003-022-03056-x
|View full text |Cite
|
Sign up to set email alerts
|

Cell density-dependent antibiotic tolerance to inhibition of the elongation machinery requires fully functional PBP1B

Abstract: The peptidoglycan (PG) cell wall provides shape and structure to most bacteria. There are two systems to build PG in rod shaped organisms: the elongasome and divisome, which are made up of many proteins including the essential MreB and PBP2, or FtsZ and PBP3, respectively. The elongasome is responsible for PG insertion during cell elongation, while the divisome is responsible for septal PG insertion during division. We found that the main elongasome proteins, MreB and PBP2, can be inhibited without affecting g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 68 publications
(108 reference statements)
0
11
0
Order By: Relevance
“…It is also unclear if MreB plays other roles in the cell, independent from regulating rod shape. We have previously reported that two gene deletions, envC and tusE , result in cells with increased sensitivity to A22, although the mechanism for this is unknown (18). Interestingly, deletion of either of these genes leads to slower growth, a condition normally thought to promote growth without MreB (Fig S1) (18).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It is also unclear if MreB plays other roles in the cell, independent from regulating rod shape. We have previously reported that two gene deletions, envC and tusE , result in cells with increased sensitivity to A22, although the mechanism for this is unknown (18). Interestingly, deletion of either of these genes leads to slower growth, a condition normally thought to promote growth without MreB (Fig S1) (18).…”
Section: Resultsmentioning
confidence: 99%
“…We further characterized the effects of A22 on each of these mutants by measuring the change in rod shape and size of the cells. Using the metric, coefficient of variation of intracellular diameter deviation (IDD), we can measure the “rodness” of cells (4, 12, 18).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations